2022
DOI: 10.3390/molecules27082488
|View full text |Cite
|
Sign up to set email alerts
|

Eriodictyol and Homoeriodictyol Improve Memory Impairment in Aβ25–35-Induced Mice by Inhibiting the NLRP3 Inflammasome

Abstract: (1) Alzheimer’s disease (AD) is a neurodegenerative disorder, and it is now widely accepted that neuroinflammation plays a key role in its pathogenesis. Eriodictyol (Eri) and homoeriodictyol (Hom), dihydroflavonoids extracted from a variety of plants, have been confirmed to display a relationship with neuroprotection. (2) Methods: An AD mouse model was constructed by intracerebroventricular (ICV) injection of the Aβ25–35 peptide, and Eri and Hom were administered orally for 4 weeks. UPLC-MS/MS was used to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…The animals used and the Aβ 25–35 intracerebroventricular (ICV) injection protocol were as reported in our previous study (Guo et al, 2022). Sixty 7‐week‐old and 40 g male Kunming mice (SCXK [Jing] 2016‐0011, Beijing Vitalstar Biotechnology Co. Ltd.) were randomly divided into the control (Con), model (M), donepezil (Don, 10 mg/kg), Piper kadsura (PK, 1.4 g/kg), low‐dose Futoquinol (Fut‐L, 15 mg/kg), and high‐dose Futoquinol (Fut‐H, 30 mg/kg) groups, with 10 mice per group.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The animals used and the Aβ 25–35 intracerebroventricular (ICV) injection protocol were as reported in our previous study (Guo et al, 2022). Sixty 7‐week‐old and 40 g male Kunming mice (SCXK [Jing] 2016‐0011, Beijing Vitalstar Biotechnology Co. Ltd.) were randomly divided into the control (Con), model (M), donepezil (Don, 10 mg/kg), Piper kadsura (PK, 1.4 g/kg), low‐dose Futoquinol (Fut‐L, 15 mg/kg), and high‐dose Futoquinol (Fut‐H, 30 mg/kg) groups, with 10 mice per group.…”
Section: Methodsmentioning
confidence: 99%
“…The order in which the mice entered each arm and the total number of arms (N) was recorded. An alternation is considered if an animal entered three different arms in a row, and the largest arm entry is defined as N‐2; percent alternation (%) = [alternation/(N − 2)] × 100% (Guo et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…5 μL of AV-FITC and 5 μL of PI were added to the cells and incubated at room temperature in the dark for 15min, and then 400 μL PBS was added to each sample. The flow cytometric analysis was performed within 1 h [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…ROS production was evaluated by the FACS flow cytometer. The level of intracellular ROS was shown as a percentage of non-treated control [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…Eriodictyol and homoeriodictyol are two dihydroflavonoids that exist widely in plants. Reports have demonstrated that these two molecules can penetrate the blood–brain barrier and ameliorate Aβ25–35-induced memory impairment in AD mice; they also inhibited NLRP3 inflammasome activation and ameliorated immune cell disorder ( Guo et al, 2022 ). Nobiletin is a naturally occurring polymethoxylated flavonoid primarily that exists in citrus peel.…”
Section: Natural Products As Potential Inflammasome Inhibitors For Th...mentioning
confidence: 99%